THE EFFECTIVENESS OF METHOD, VIDEO, IMAGE, AND SONG ON HAND WASHING BEHAVIOR IN 1ST-3RD GRADERS OF SDIT PERMATA MULIA MOJOKERTO - Yulianto Yulianto; Yufi Aris Lestari; Hartin Hartin Suidah; Nur Nur Chasanah; Nanik Nur Rosyidah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
ABSTRACT Introduction: Hand washing is an activity of removing microorganism from hand using soap and flowing water. Video, image, and song methods are the ones that can be used for school-age children to provide health education about hand washing. The objective of research was to find out the effectiveness of video, image, and song methods on hand washing behavior. Method: This study was a research using Pre-experiment design with pre-post test design, the one using causal relationship without control group participation. The population of research consisting of 90 students. Technique of analyzing data used was to compare mean scores of video, image, and song methods. Result: The result of research showed that the mean score of hand washing ability in video group was 2.183 before intervention and 5.727 after intervention; there was an increase by 3.545 point in the mean score of hand washing ability. In Image group, the mean score of hand washing ability was 2.273 before intervention and 4.545 after intervention; there was increase by 2.273 in the mean score of hand washing ability. Meanwhile, in song group, the mean score of hand washing ability was 2.273 before intervention and 6.00 after intervention; there was increase by 3.727 in the mean score of hand washing ability. Analysis and Discussion: Respondents in song group had highest increase in the hand washing ability compared with those in video and image groups. Song method could be an alternative choice for hand washing practice.